The coping strategies employed by rural households during the economic crisis in Zimbabwe, 2008-2009 - Munetsi, Prosper (2017)
The study explores the coping strategies employed by rural households during an economic crisis. The essential part of this research was to explore the impacts of the economic crisis and the strategies which were employed during the economic crisis in Zimbabwe in the period of 2008-2009. Further suggestion measures to enhance the resilience of rural households’ in future economic crisis were presented. A qualitative research approach was used by the researcher with unstructured and structured interviews as data collecting tools. The researcher found out that the strategies employed were based on available resources on household level and their access to basic livelihood resources on community level.